Pseudo-rotational motion of cyclic molecules and thermal conductivity of tetrahydrofuran - Konstantinov, V.A.; Sagan, V.V.; Revyakin, V.P.; Karachevtseva, A.V. (Recent Contributions to Physics, 2015)
Pseudo-rotation is a large amplitude motion arising from the interaction of two degenerate, or nearly degenerate out-of-plane ring puckering modes in the presence of a small barrier to planarity of the molecule [1]. Pseudo-rotation in tetrahydrofuran (THF), C4H8O, arises from near cancellation of the angular strain forces due to nontetrahedral bond angles in the skeleton ring and torsional forces due to hydrogen-hydrogen repulsion.